Cultura tributaria en los estudiantes de la Escuela superior de formación artística pública Lorenzo Lujan Darjon de Iquitos, periodo 2023 - Paredes Macedo, Maria Emily (2023)
The tax culture is that action through which human behavior is conditioned regarding the fulfillment of their tax duties and obligations, the latter being directly associated with the knowledge, education and values that people must possess to comply with the commitments. of a tax nature. The research is entitled "Tax Culture in the students of the Lorenzo Lujan Darjon public artistic training higher school in Iquitos, period 2023", whose main objective is to determine the level of tax culture that the students present with respect to the study period, their study It is of a quantitative type and a descriptive cross-sectional design, the survey technique was used and the questionnaire of questions was used as an instrument, which was applied to a sample comprised of 66 individuals. Finally, from the analysis of the data collected, it was possible to determine that the students present a medium level of tax culture, which reached an average level of 50%.